Academic freedom in the ‘incentivised university: The case of South Africa - Muller, S. (South African Journal of Higher Education, 2025)
In the Incentivised University (2021), Muller argues that the current dominant approach to higher education systems based on “incentivisation” is both philosophically and practically flawed. This article examines the issue of academic freedom in South Africa through the lens of that critique, although its analysis and prescriptions are likely to be relevant to other countries as well. While academic freedom is enshrined in the South African Constitution, the structure and functioning of the higher education system – and the conduct of universities – is driven by an incentive-based framework. The article argues that there is an irreconcilable tension between the “incentivised university” and academic freedom. In many respects, South Africa exemplifies this through the low priority given to academic freedom by university management, and institutional cultures that are hostile to internal dissent or criticism. The article proposes six steps to substantively embody academic freedom in universities: explicitly recognise that academic freedom extends to internal matters and individual academics, and is not just a matter of guarding institutional autonomy from external interference; reorient universities towards institutional cultures that substantively embody academic freedom rather than being driven by extrinsic incentives; change the funding system; designate and empower an independent institution outside universities to conduct regular institutional surveys of the state of academic freedom; educate and train all those within academic institutions on academic freedom; and create an independent body, with investigative and enforcement powers, to deal with violations of academic freedom.